(untitled) (CAHIERS MAGELLANES-NS, 2024)
We evaluated the antibacterial activity and chemical components of Artemisia argyi essential oil. A clevenger device extracted essential oil from Chinese mugwort, Artemisia argyi, a medicinal herb. This study examines Artemisia Argyi essential oil's antibacterial and antioxidant effects in vitro. Gas chromatography-mass spectrometry analysis. The essential oils were dominated by cis-chrysanthenol, 2-naphthalenemethanol, and pinocarvone. We tested the essential oil's antibacterial activity against harmful microbes using disc diffusion. A. argyi essential oil has excellent antibacterial action against Gram-positive and Gram-negative bacteria, including Staphylococcus aureus and E. coli. We further measured the essential oil's antioxidant activity using DPPH and ABTS radical scavenging tests. A. argyi essential oil showed excellent antioxidant activity (IC50 = 35.6 g/mL), suggesting its potential as a natural antioxidant. Because of its phytochemical content, A. argyi essential oil may have antibacterial and antioxidant activities. Understanding the modes of action and medicinal and food uses of A. argyi essential oil requires further research.